2003
DOI: 10.1109/mcom.2003.1232240
|View full text |Cite
|
Sign up to set email alerts
|

Bringing communication networks on a chip: test and verification implications

Abstract: In this article we present test and verification challenges for system chips that utilise on-chip networks. These systems on a chip (SOCs) and networks on a chip (NOCs) are introduced, where the NOC is exemplified by Philips's AETHEREAL NOC architecture. We discuss existing test and verification methods for SOCs and NOCs, and show the particular advantages of using a NOC both for testing and verifying the network, and for testing and verifying the other components of the SOC. This paper is concluded with our e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(45 citation statements)
references
References 11 publications
0
45
0
Order By: Relevance
“…The current Network-on-Chip (NoC) designs such as the ring-and bus-based topologies [39] provide an energy and throughput efficient solution for communication within small multi-cores. Since these traditional approaches for NoC's do not scale for many-cores, it is required to explore novel and scalable NoC approaches such as wireless interconnects, which can be used in conjunction with traditional wired and optical interconnects in novel RAA NoC topolo- Figure 3.…”
Section: Runtime-aware Architecturesmentioning
confidence: 99%
“…The current Network-on-Chip (NoC) designs such as the ring-and bus-based topologies [39] provide an energy and throughput efficient solution for communication within small multi-cores. Since these traditional approaches for NoC's do not scale for many-cores, it is required to explore novel and scalable NoC approaches such as wireless interconnects, which can be used in conjunction with traditional wired and optical interconnects in novel RAA NoC topolo- Figure 3.…”
Section: Runtime-aware Architecturesmentioning
confidence: 99%
“…Recently, a number of different research groups suggested the reuse of the communication infrastructure as a TAM [5], [6], [35]. Vermeulen et al [7] assumed the NoC fabric as fault-free and subsequently used it to transport test data to the functional blocks; however, for large systems, this assumption can be unrealistic, considering the complexity of the design and communication protocols. Nahvi and Ivanov [8] proposed a dedicated TAM based on an on-chip network, where network-oriented mechanisms were used to deliver test data to the functional cores of the SoC.…”
mentioning
confidence: 99%
“…However, as the number of embedded cores in the system increases, the implementation of an efficient and effective communication architecture among cores is becoming the new bottleneck of SoC performance. Traditional broadcasting or shared-bus architecture has been shown unable to supply the new-generation SoC systems with both sufficient bandwidth and low latency under a stringent power-consumption limitation [8], [12], [23], [26].…”
mentioning
confidence: 99%